PENDIDIKAN KARAKTER DAN TANTANGANNYA DI ERA DIGITAL: PERSPEKTIF PEMIKIRAN KI HADJAR DEWANTARA - Bunan Dafa Dzaki Ariza; Eko Handoyo; Tutik Wijayanti (STKIP Subang, 2026)
Character education in the digital era faces significant challenges due to the rapid advancement of technology, social media, and online learning platforms that influence students’ behavior and moral development. Although digital transformation provides wide access to information and learning resources, it also contributes to issues such as cyberbullying, misinformation, declining digital ethics, and gadget dependency. This study aims to analyze Ki Hadjar Dewantara’s perspective on character education and examine its relevance in addressing the challenges of the digital era. The research employs a library research method in the form of a figure study, utilizing primary sources from Ki Hadjar Dewantara’s original works and secondary sources from relevant scholarly articles and research findings. Data were collected through documentation techniques and analyzed using content analysis to identify key concepts and their contextual implementation in modern education. The findings reveal that Ki Hadjar Dewantara’s concept of character education, which emphasizes the balanced development of cipta (intellect), rasa (emotion), and karsa (will), as well as the principles of Ing Ngarso Sung Tulodo, Ing Madya Mangun Karso, and Tut Wuri Handayani, remains highly relevant. These principles provide a moral foundation for integrating technology into education while maintaining ethical and humanistic values.